Adolescents’ Health Literacy and Decision-making: A Qualitative Study - Fleary, Sasha A. (Am J Health Behav, 2020)
OBJECTIVE: Adolescents assume increased responsibility for their health, particularly regarding health decision-making for lifestyle behaviors. Prior research suggests a relationship between health literacy (HL) and health behaviors in adolescents. Yet, the specific role of HL in adolescents’ health decision-making is unclear. This study qualitatively explored adolescents’ use of HL in their health decision-making. METHODS: Six focus groups with adolescents (N = 37, M(age) = 16.49, 86% girls) were conducted. Adolescents’ responses to questions about their HL use were coded using thematic analysis. RESULTS: Adolescents identified passive and active HL engagement and several individual (eg, future orientation, risk perception) and environmental (eg, access to resources/information, media) factors that influenced their use of HL in health decision-making. Feedback from others, subjective health, and ability to navigate multiple sources of information also determined adolescents’ confidence in their HL skills. CONCLUSIONS: Our results support expanding the types of HL studied/measured in adolescents and provide insight on how HL can be leveraged to improve adolescents’ health decision-making. Though there was no guiding theory for this study, results support using the Information-Motivation-Behavior Skills model to assess the HL/health decision-making relationship in adolescence.